Perspektif Dibalik Perilaku Living Together di Kalangan Mahasiswa di Kota Semarang - Aprilian Dani Bagus Setiawan; Putri Gevira; Rauly Sijabat (INDO PUBLISHING, 2026)
This study aims to determine the perspectives behind cohabitation behavior among students in Semarang City. This study uses a qualitative approach with a phenomenological method. The results of the study can be drawn several conclusions as follows: (a) Subjective Perspective and Meaning: Student actors interpret cohabitation not merely as a deviation, but as a form of